A new species of Moutabea (Polygalaceae) for the Brazilian Amazon, Guyana and Peru - Silveira, João Barros; Secco, Ricardo De S. (Phytotaxa, 2015)
As part of the review of Moutabea, a new species of the genus, Moutabea floribunda, is described and illustrated. It is characterized by its smooth leaves with adaxially lustrous surface, racemes with rachis trimerous or tetramerous, monads rare, and pubescent seeds with unnoticeable raphe. This paper contains a description, a comparison with similar species, illustrations, distribution map, and phenological information about the new species.